Study on the feasibility of a tool to measure the macroeconomics impact of structure reforms - Dreger, Christian.; Artis, Manuel.; Moreno, Rosina.; Ramos, Paul.; Surinach, Jordi.; European Commission : Directorate-General for Economic and Financial Affairs. (European Economy. Economic papers, 2007)
The main aim of this study is to assess the feasibility of empirical tools to study the impact of structural reforms on the macroeconomic performance in the member countries of the European Union (EU). This report presents the results of the project "Study on the feasibility of a tool to measure the macroeconomic impact of structural reforms" (ECFIN-E/2005/001) and amalgamates the findings of the two previous interim reports and the main conclusions of the workshop held in Brussels on May 11th. The main goal of the project is to determine the most reliable and robust methods to investigate the impacts of economy-wide structural reforms as well as reforms in individual markets or sectors, and to make suggestions as to how they best to implement them and possible improvements of the institutional dataset. In addition, a roadmap has been created which includes the main steps in the model-developing process, and solutions feasible even in the short term are discussed. The most relevant conclusion to be drawn from the study is that the most appropriate tool that can be developed in the short term is the integration of a DSGE model (preferably QUEST due to its in-house availability) with different satellite models, to be developed.